Aviation biofuel from integrated woody biomass in southern Australia - McGrath, Jeff; Goss, K.; Brown, M.; Bartle, J.; Abadi, A. (John Wiley & Sons, 2017)
A synthesis of work on integrating short‐rotation biomass plantings into existing mixed crop and livestock farming regimes with the biomass being converted to biofuels, including aviation fuel, is provided. This agroforestry system, based on mallee eucalypt species native to Australia, provides broader environmental benefits, including biodiversity protection. These species are suited to the edaphic and climatic conditions of rainfed farming systems in southern Australia. The study focused on the Great Southern region of Western Australia, with an average annual rainfall of 400–600 mm. Compared to other locations in Australia, significantly more research and development has been conducted in this region, with a mallee biomass‐to‐jet fuel business case and farmer cooperation providing reliable data for assessing the viability and sustainability of commercial supply chain development. The limited capacity of Australian agricultural systems to produce biomass due to the relatively dry climate means that the available biomass resources should be directed to strategically important energy uses such as aviation fuel. Technical, economic, and environmental insights gained from these long‐term studies have demonstrated that it is feasible to integrate this new production system into the overall farming enterprise and indicate strong prospects for a biomass industry in this region should political and economic uncertainties currently facing the renewable energy industry in Australia be resolved.